Adding glucose combined with microalgae to water improves the benefits of the fungal community on the whiteleg shrimp (Litopenaeus vannamei) culture - Bilal Raza; Jiangdong Ke; Lin Chen; Yikai Shi; Jinyong Zhu; Zeyu Shao; Zhongming Zheng; Kaihong Lu; Wen Yang (Aquaculture Reports)
In shrimp aquaculture systems, the introduction of carbon sources or microalgae into rearing water has shown potential for improving the microenvironment and enhancing shrimp health. However, the effectiveness of combining both carbon sources and microalgae, as well as their impacts on the fungal community, remains uncertain. In this study, glucose and Nannochloropsis oculata were added together to the aquaculture system to investigate their effects on fungal community in rearing water and shrimp health. The results revealed that the combined addition significantly changed the composition and structure and of the fungal community, specifially increasing the relative abundance of fungi linked with the genus Aspergillus. Moreover, Aspergillus was indentified as both the biomarkers and modular nodes in co-occurrence network, domonstrating its strong association with non-specific immune enzyme activities of shrimp. Network topology analysis showed that the N. oculata and glucose combined promoted the complexity and amplified the proportion of negative edges in the fungal network, thereby enhacing the stability of the fungal community. Partial least squares path modeling (PLS-PM) analysis further demonstrated that both the composition and network topology of the fungal community significantly influenced shrimp survival rates. These findings offer a comprehensive understanding of microbial ecology and management techniques in shrimp aquaculture systems, contributing to the creation of a healthier culture environment.